Chronic diseases and mortality among hospitalised COVID-19 patients at Bafoussam Regional Hospital in the West region of Cameroon. - Imelda Sonia Nzinnou Mbiaketcha; Collins Buh Nkum; Ketina Hirma Tchio-Nighie; Iliasou Njoudap Mfopou; Francois Nguegoue Tchokouaha; Jérôme Ateudjieu (Public Library of Science (PLoS), 2023)
Reducing mortality among COVID-19 cases is a major challenge for most health systems worldwide. Estimating the risk of preexisting comorbidities on COVID-19 mortality may promote the importance of targeting at-risk populations to improve survival through primary and secondary prevention. This study was conducted to explore the contribution of exposure to some chronic diseases on the mortality of COVID-19. This was a case control study. The data were collected from the records of all patients hospitalised at Bafoussam Regional Hospital (BRH) from March 2020 to December 2021. A grid was used to extract data on patient history, case management and outcome of hospitalised patients. We estimated the frequency of each common chronic disease and assessed the association between suffering from all and each chronic disease (Diabetes or/and Hypertension, immunodeficiency condition, obesity, tuberculosis, chronic kidney disease) and fatal outcome of hospitalised patients by estimating crude and adjusted odd ratios and their corresponding 95% confidence intervals (CI) using time to symptom onset and hospital admission up to three days, age range 65 years and above, health professional worker and married status as confounder's factors. Of 645 included patients, 120(20.23%) deaths were recorded. Among these 645 patients, 262(40.62%) were males, 128(19.84%) aged 65 years and above. The mean length of stay was 11.07. On admission, 204 (31.62%) patients presented at least one chronic disease. The most common chronic disease were hypertension (HBP) 73(11.32%), followed by diabetes + HBP 62 (9.61%), by diabetes 55(8.53%) and Immunodeficiency condition 14(2.17%). Diabetes and Diabetes + HBP were associated with a higher risk of death respectively aOR = 2.71[95%CI = 1.19-6.18] and aOR = 2.07[95% CI = 1.01-4.23] but HBP did not significantly increased the risk of death. These results suggest that health authorities should prioritize these specific group to adopt primary and secondary preventive interventions against SARS-CoV-2 infection.